Automorphism groups of Cayley digraphs of ${\Bbb Z}_p^3$ - Dobson, Edward; Kovács, István (The Electronic Journal of Combinatorics, 2009)
We calculate the full automorphism group of Cayley digraphs of ${\Bbb Z}_p^3$, $p$ an odd prime, as well as determine the $2$-closed subgroups of $S_m \wr S_p$ with the product action.